The Influence of Traditional Balinese Cuisine Quality on Tourist Interests in Badung Regency - Sindy Claudya; Ni Made Tirtawati; Ni Putu Oka Agustini (Gastronomy Tourism Journal, 2022)
Traditional Balinese cuisine is food that is processed by local people for generations by using a blend of local spices. The cuisines as culinary tourism enrich Balinese culture. The quality of the cuisines in each region specialties also matter as they can attract tourists to visit Bali not only for its natural beauty, but also because of the fascinating and varied culinary delights. Therefore, this study aims to see the effect of the quality of traditional Balinese cuisines on the interest of tourists visiting Badung regency. The data analysis method used is instrument test, descriptive statistics, classical assumption test, multiple linear regression test and hypothesis testing where data collection is done through questionnaires with a total sample of 102 domestic tourist respondents. The sampling technique used purposive accidental sampling through several considerations. The results of this study showed that partially, there was no significant effect of traditional Balinese cuisine on freshness,  and presentation variables on visiting interest, while well cooked and variety of food, variables show a significant effect on interest in visiting. Simultaneously, traditional Balinese cuisines has a significant influence on the interest of domestic tourists to visit destinations in Badung Regency.